(untitled) (Herald of Journalism, 2016)
The article is devoted to the study of works of new personalities in the frames of training course of Foreign Journalism. The attention focuses on texts of J. Barnes, U. Eco, book-interview of V. Gorbulin, book-dialogue F. Stern and H. Schmidt. Was initiated an attempt to present models of future of journalism on the basis of analysis of foreign researches.